Planning the Modern Public Library Building (Libraries Unlimited Library Management Collection) - McCabe, Gerard B. (Libraries Unlimited, 2012)
This collection of 22 highly informative essays offers important insight into current activities in the area of building planning. Written by recognized building experts from the United States and Australia, the essays discuss critical planning issues from a management perspective. Topics include space design; collection marketing; furniture selection; landscaping; accommodating different age groups; hosting activities and events; seeking support from the community; and more. Technology is given a high priority. A bibliographic essay provides an abundance of suggested titles for further study.